Endoscopic Release of the Carpal Ligament: A Sheathless Tube Technique for Carpal Tunnel Syndrome - Wei Xiang, M.D.; Ri Zhou, M.D.; Hongyu Li, M.D.; Shiyou Ren, M.D.; Mengjun Ma, M.D.; Wentao Zhang, M.D. (Arthroscopy Techniques)
Minimally invasive techniques have become the standard of care for multiple procedures. Our sheathless tube technique makes minimally invasive techniques for carpal tunnel syndrome simpler and offers reduced incision pain, improved aesthetic outcomes, and shorter recovery time. The technique involves using the palmar longus tendon to create the operative space while using it as a guide to release the transverse carpal ligament and achieve nerve decompression. The surgical outcome is comparable with other traditional methods. The conventional approach involves a contrasting perspective, by contrast, our incision and operation are performed on the same side, making it significantly more manageable to acquire mastery. Therefore, this technique represents a viable approach for carpal tunnel release without special equipment.